Determining Dynamic On-resistance of Lateral Gallium Nitride Devices in Motor Driver Applications - Zhu, Daihui; Josefsson, Mikael (My University, 2025)
Abstract This report investigates different challenges of determining the effects of dynamic on-resistance (D-Rds(on)) in lateral Gallium Nitride High Electron Mobility Tran-sistors (GaN-HEMT) operated in automotive traction inverter conditions. A lit-erature review identifies the operational parameters of the devices that affect D-Rds(on) most adversely. The accuracy, complexity, and testable operational pa-rameters of different measurement methods, i.e., double pulse test, multi-pulse test, and steady-state continuous switching, are investigated. The report also examines different on-state voltage measurement circuits (OVMCs) needed to measure D-Rds(on) accurately. The report concludes that operational parameters, such as drain-to-source voltage, drain current, switching frequency, duty cycle,and turn-on gate resistance, significantly influence D-Rds(on). Moreover, these pa-rameters exhibit a synergistic relationship. In contrast, the impact of junction temperature on D-Rds(on) is ambiguous and varies between studies. Additionally, D-Rds(on) varies with production batches and device structures. Further, a double pulse test is a suitable first method to determine whether a device suffers from D-Rds(on). If accuracy is prioritized, the multi-pulse test serves as an alternative method. Finally, two different OVMCs are concluded to have sufficient perfor-mance for determining D-Rds(on).